Impacts of COVID-19 on contraceptive and abortion services in low- and middle-income countries: a scoping review. Issue 1 (31st December 2022) - Polis, Chelsea B.; Biddlecom, Ann; Singh, Susheela; Ushie, Boniface Ayanbekongshie; Rosman, Lori; Saad, Abdulmumin
Abstract: The COVID-19 pandemic has disproportionate effects on people living in low- and middle-income countries (LMICs), exacerbating weak health systems. We conducted a scoping review to identify, map, and synthesise studies in LMICs that measured the impact of COVID-19 on demand for, provision of, and access to contraceptive and abortion-related services, and reproductive outcomes of these impacts. Using a pre-established protocol, we searched bibliographic databases (December 2019–February 2021) and key grey literature sources (December 2019–April 2021). Of 71 studies included, the majority (61%) were not peer-reviewed, and 42% were based in Africa, 35% in Asia, 17% were multi-region, and 6% were in Latin America and the Caribbean. Most studies were based on data through June 2020. The magnitude of contraceptive service-related impacts varied widely across 55 studies (24 of which also included information on abortion). Nearly all studies assessing changes over time to contraceptive service provision noted declines of varying magnitude, but severe disruptions were relatively uncommon or of limited duration. Twenty-six studies addressed the impacts of COVID-19 on abortion and postabortion care (PAC). Overall, studies found increases in demand, reductions in provision and increases in barriers to accessing these services. The use of abortion services declined, but the use of PAC was more mixed with some studies finding increases compared to pre-COVID-19 levels. The impacts of COVID-19 varied substantially, including the country context, health service, and population studied. Continued monitoring is needed to assess impacts on these key health services, as the COVID-19 pandemic evolves.